Bentuk Penyajian Musik Tradisional Tuddukat dalam Ritual Arat Sabulungan di Kepulauan Mentawai - Elbertin Chrismenta Siritoitet; Moh Sarjoko (Departement of Mathematics Education, 2024)
This research aims to describe the form of presentation of traditional Tuddukat music in the Arat Sabulungan ritual in the Mentawai Islands. This research took place in the Mentawai Islands. The Arat Sabulungan ritual acts as an intermediary between the world of spirits and humans. This causes Tuddukat not only to function as a means of communication between tribe members, but also as a means of communication with the spirit world. This research uses qualitative analysis techniques aimed at collecting data, interviews and documentation regarding the form of presentation and meaning of Tuddukat poetry in the Arat Sabulungan ritual. The traditional Tuddukat music of the Mentawai tribe, Tuddukat is made from kulib forest wood or Babaet, Tuddukat consists of 3 kentongan, namely (1) Ina Tuddukat as the parent (2) Middle Sileleite Tuddukat, (3) Toga Tuddukat child. Tuddukat play an important role in survival, they express their feelings, such as sadness, joy, sorrow, which are played out in every Tetabuhan. The research results show that the form of presentation of Tuddukat music in the Mentawai Islands is as a medium for emotional expression for Tuddukat players, as entertainment for the audience, as aesthetic satisfaction for the community, as a means of long-distance communication conveying moral messages. The Arat Sabulungan ritual acts as an intermediary between the world of spirits and humans. This causes Tuddukat not only to function as a means of communication between tribe members, but also as a means of communication with the spirit world. The meaning contained in the Tuddukat poetry is the feeling of joy that can be felt by the people who watch it as well as the positive impact of playing or listening to the Tuddukat drumming, while the Tuddukat players themselves experience the Arat Sabulungan ritual.